The importance of reinforcing advanced ceramics in space projects (International Seven Journal of Multidisciplinary, 2024)
This article addresses the role of advanced ceramics in space exploration, highlighting their importance in tackling the unique challenges of the extraterrestrial environment. Starting with an analysis of the Space Shuttle Columbia disaster in 2003, lessons learned and safety measures implemented in the aftermath of the incident are discussed. The properties of advanced ceramics, including resistance to extreme temperatures, chemical stability, and thermal insulation capability, are explored, along with their applicability in space missions, such as radiation protection, resistance to debris, and propulsion. Strategies for maximizing the resilience of ceramics in space environments are examined, including advanced manufacturing techniques and continuous monitoring systems. Finally, specific applications of ceramics in space components, such as rocket nozzles, propulsion systems, and heat-to-electricity conversion, are discussed, emphasizing the ongoing need for innovation to ensure the success of future space missions.